Cellular Senescence in Kidney Fibrosis: Pathologic Significance and Therapeutic Strategies - Xu, Jie; Zhou, Lili; Liu, Youhua (Frontiers in Pharmacology, 2020)
Age-related disorders such as chronic kidney disease (CKD) are increasingly prevalent globally and pose unprecedented challenges. In many aspects, CKD can be viewed as a state of accelerated and premature aging. Aging kidney and CKD share many common characteristic features with increased cellular senescence, a conserved program characterized by an irreversible cell cycle arrest with altered transcriptome and secretome. While developmental senescence and acute senescence may positively contribute to the fine-tuning of embryogenesis and injury repair, chronic senescence, when unresolved promptly, plays a crucial role in kidney fibrogenesis and CKD progression. Senescent cells elicit their fibrogenic actions primarily by secreting an assortment of inflammatory and profibrotic factors known as the senescence-associated secretory phenotype (SASP). Increasing evidence indicates that senescent cells could be a promising new target for therapeutic intervention known as senotherapy, which includes depleting senescent cells, modulating SASP and restoration of senescence inhibitors. In this review, we discuss current understanding of the role and mechanism of cellular senescence in kidney fibrosis. We also highlight potential options of targeting senescent cells for the treatment of CKD.